Alveolar wound healing after implantation with a pool of commercially available bovine bone morphogenetic proteins (BMPs): a histometric study in rats - Calixto,Romeu Felipe Elias (2007)
The capacity of a commercially available pool of bovine bone morphogenetic proteins (BMPs) to stimulate osteogenesis in the rat alveolar healing was investigated by histometric analysis. Male rats were anesthetized and had their upper incisor extracted. A pool of purified bovine BMPs adsorbed to microgranular resorbable hydroxyapatite was agglutinated with bovine collagen and saline before implantation into the alveolar socket. The implanted and control rats (n=30 per group) were sacrificed 1 to 9 weeks postoperatively, the hemi-maxillae were decalcified, processed for paraffin embedding and semi-serial longitudinal sections were obtained and stained with hematoxylin and eosin. The volume fraction of alveolar healing components was estimated by a differential point-counting method in histologic images. The results showed that in both, control and implanted rats, the alveolar healing followed the histologic pattern usually described in the literature. Quantitative data confirmed that the BMPs mixture did not stimulate new bone formation in the alveolar socket of implanted rats. These results suggest that the pool of BMPs adsorbed to hydroxyapatite and agglutinated with bovine collagen did not warrant incorporation of the osteoinductive proteins to a slow-absorption system that would allow a BMPs release rate compatible to that of new bone formation, and thus more adequate to osteoinduction.